2018
DOI: 10.3390/coatings8120423
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Functional Properties of Bee Pollen: The Case of “Bee Pollen Yoghurt”

Abstract: The objectives of the present work were: (a) to characterize bee pollen from the region of Epirus in terms of biofunctional activity parameters as assessed by (i) the determination of specific polyphenols using high performance liquid chromatography electrospray ionization mass spectrometry (HPLC/ESI-MS), (ii) antioxidant capacity (DPPH assay), and (iii) total phenolic content (Folin-Ciocalteu assay), and (b) to prepare yoghurts from cow, goat, and sheep milk supplemented with different concentrations of groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 27 publications
2
31
0
3
Order By: Relevance
“…To meet this demand, bioactives have been developed in the past, but only a few that are useful in the encapsulation of probiotic ingredients have been added to food or nutraceutical products. In particular, probiotic bacteria have received considerable interest and their incorporation into food is growing [3]. The challenge of these functional foods is to preserve the functionality of the bacteria present and to ensure that they reach the site of their activity in sufficient quantity.…”
Section: Introductionmentioning
confidence: 99%
“…To meet this demand, bioactives have been developed in the past, but only a few that are useful in the encapsulation of probiotic ingredients have been added to food or nutraceutical products. In particular, probiotic bacteria have received considerable interest and their incorporation into food is growing [3]. The challenge of these functional foods is to preserve the functionality of the bacteria present and to ensure that they reach the site of their activity in sufficient quantity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Yerlikaya [28] observed an increase of total solids (from 9.0% ± 0.1% to 10.1% ± 0.1%), proteins (from 3.4% ± 0.1% to 3.6% ± 0.02%), and proteolytic activities (from 0.6 ± 0.28 to 1.5 ± 0.25 expressed as free amino acids equivalents) and a decrease in the content of fat (from 1.6% ± 0.1% to 1.4% ± 0.1%) in the fermented milk beverages supplemented with the commercial bee pollen in a concentration range from 2.5 to 20 mg/mL. Karabagias et al [24] showed that the total phenolic content and in vitro antioxidant capacity of the yogurts enriched with bee pollen depend on the concentrations of pollen (0.5; 1.0; 2.5; 3.0% w/v), and they significantly varied in cow (2882.5 ± 1.31 to 7771.5 ± 2.29 mg GAE/L and 71.9% ± 0.02% to 98.79% ± 0.01% inhibition of DPPH radical, respectively), sheep (2900.3 ± 2.25 to 8780 ± 2.25 mg GAE/L and 74.65% ± 0.01% to 99.69% ± 0.01% inhibition of DPPH radical, respectively), and goat (2198.3 ± 1.53 to 7490.5 ± 0.5 mg GAE/L and 71.5% ± 0.01% to 95.91% ± 0.02% inhibition of DPPH radical, respectively) yogurts. Based on the detailed antioxidant and sensory characterization data the "bee pollen yogurts" have been proposed as a new biofunctional food, with the potential for treating chronic human health conditions.…”
mentioning
confidence: 98%
“…Based on the detailed antioxidant and sensory characterization data the "bee pollen yogurts" have been proposed as a new biofunctional food, with the potential for treating chronic human health conditions. However, these hypotheses need to be confirmed by clinical in vivo studies [24].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…is result was higher than other reported studies of food fortified with bee pollen. For example, phenolic content in sheep milk yoghurt enriched with bee pollen was 8.78 mg GAE/g [25]. In another study, Krystyjan et al [26] reported 4.84 mg GAE/g in 10% bee pollen biscuits while Conte et al [22] only reported a maximum of 4.42 mg GAE/g in 5% bee pollen bread.…”
Section: Total Phenolic Content and Total Flavonoid Contentmentioning
confidence: 97%